Characterization of IDH1 p.R132H Mutant Clones Using Mutation-specific Antibody in Myeloid Neoplasms. (May 2018) - Kurt, Habibe; Bueso-Ramos, Carlos E.; Khoury, Joseph D.; Routbort, Mark J.; Kanagal-Shamanna, Rashmi; Patel, Umang V.; Jorgensen, Jeffrey L.; Wang, Sa A.; Ravandi, Farhad; DiNardo, Courtney; Luthra, Rajyalakshmi; Medeiros, L. Jeffrey; et al.
Abstract : Isocitrate dehydrogenase 1 ( IDH1 ) and IDH2 mutations occur in a variety of myeloid neoplasms. Immunohistochemistry (IHC)-based direct visualization of mutant clones of hematopoietic cells can be useful for rapid diagnostic screening and for monitoring treatment response. In this study, we first evaluated the sensitivity and specificity of the IDH1 p.R132H mutation-specific antibody by IHC. All IDH1 wild type cases (n=11) and IDH1 mutant cases with a non-p.R132H mutation (n=30) were negative by IHC, demonstrating 100% antibody specificity. All the initial diagnostic specimens with IDH1 p.R132H mutation including acute myeloid leukemia (n=30), myelodysplastic syndromes (MDS) (n=10), MDS/myeloproliferative neoplasms (MPN) (n=4), and MPN (n=5) were positive by IHC, demonstrating 100% antibody sensitivity. Both immature and mature myeloid cells showed immunoreactivity. Erythroid precursors, lymphoid cells, endothelial cells, and osteoblasts were consistently negative by IHC. We then evaluated the follow-up specimens with a known IDH1 mutation status including acute myeloid leukemia (n=23), MDS (n=2), MDS/MPN (n=2), and MPN (n=2). Thirty-three IDH1 p.R132H mutant cases were positive by IHC and 12 IDH1 mutation negative cases were negative by IHC. However, IHC reactivity in up to 25% of bone marrow cells was noted in 8 of 20 polymerase chain reaction-negative cases, all from patients with a known history of IDH1 p.R132H mutation indicating sampling error or a sensitivity issue with molecular tests. These data indicate that IHC is a highly specific and sensitive tool to detect IDH1 p.R132H mutation in bone marrow involved by myeloid neoplasms. In addition, IDH1 p.R132H IHC also allows localization and assessment of the maturation stage of the clones carrying the mutation.